Changes in El Niño – Southern Oscillation (ENSO) conditions during the Greenland Stadial 1 (GS-1) chronozone revealed by New Zealand tree-rings. (1st December 2016) - Palmer, Jonathan G.; Turney, Chris S.M.; Cook, Edward R.; Fenwick, Pavla; Thomas, Zoë; Helle, Gerhard; Jones, Richard; Clement, Amy; Hogg, Alan; Southon, John; Bronk Ramsey, Christopher; Staff, Richard; et al.
Abstract: The warming trend at the end of the last glacial was disrupted by rapid cooling clearly identified in Greenland (Greenland Stadial 1 or GS-1) and Europe (Younger Dryas Stadial or YD). This reversal to glacial-like conditions is one of the best known examples of abrupt change but the exact timing and global spatial extent remain uncertain. Whilst the wider Atlantic region has a network of high-resolution proxy records spanning GS-1, the Pacific Ocean suffers from a scarcity of sub-decadally resolved sequences. Here we report the results from an investigation into a tree-ring chronology from northern New Zealand aimed at addressing the paucity of data. The conifer tree species kauri ( Agathis australis ) is known from contemporary studies to be sensitive to regional climate changes. An analysis of a 'historic' 452-year kauri chronology confirms a tropical-Pacific teleconnection via the El Niño – Southern Oscillation (ENSO). We then focus our study on a 1010-year sub-fossil kauri chronology that has been precisely dated by comprehensive radiocarbon dating and contains a striking ring-width downturn between ∼12, 500 and 12, 380 cal BP within GS-1. Wavelet analysis shows a marked increase in ENSO-like periodicities occurring after the downturn event. Comparison to low- and mid-latitude Pacific records suggests a coherency with ENSO and Southern Hemisphere atmospheric circulation change during this period. The driver(s) for this climate event remain unclear but may be related to solar changes that subsequently led to establishment and/or increased expression of ENSO across the mid-latitudes of the Pacific, seemingly independent of the Atlantic and polar regions. Highlights: New Zealand tree-rings identify century-duration climate shift ∼12, 500–12, 380 cal BP within the Greenland Stadial-1 chronozone. El Niño - Southern Oscillation expressed Pacific Ocean-wide after ∼12, 380 cal BP. Pacific-wide change appears not to be driven by the North Atlantic.